Thermodynamics of calmodulin binding to cardiac and skeletal muscle ryanodine receptor ion channels - Meissner, Gerhard (2009)
The skeletal muscle (RyR1) and cardiac muscle (RyR2) ryanodine receptor calcium release channels contain a single, conserved calmodulin (CaM) binding domain, yet are differentially regulated by CaM. Here, we report that high-affinity [(35)S]CaM binding to RyR1 is driven by favorable enthalpic and entropic contributions at Ca(2+) concentrations from <0.01 to 100 μM. At 0.15 μM Ca(2+), [(35)S]CaM bound to RyR2 with decreased affinity and binding enthalpy compared with RyR1. The rates of [(35)S]CaM dissociation from RyR1 increased as the temperature was raised, whereas at 0.15 μM Ca(2+) the rate from RyR2 was little affected. The results suggest major differences in the energetics of CaM binding to and dissociation from RyR1 and RyR2.